PECULIARITIES OF THE SEISMIC RISK OF THE DESTRUCTIVE EARTHQUAKE ZONE (7.5>M>7.0): (on example of the 1988 Spitak Earthquake) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The features of changes in the seismic risk of a zone of a strong earthquake, associated with both its destructive consequences and the processes of recovery of the earthquake zone, are considered. This problem has not been studied enough despite its importance for risk assessment and mitigation. To achieve the main goal, the problem is considered on the basis of the change in the risk of the 1988 Spitak Earthquake zone. It is proposed to divide the earthquake zone into subzones, taking into account the scale of destruction of buildings, which makes it possible to more reliably establish general and local peculiarities of risk changes. It is concluded that for various reasons, the risk of the territory of the cities in the subzone of strong destruction is significantly reduced, and vice versa, it will increase in the subzones of medium and weak destruction.
Keywords: earthquake; vulnerability; risk; recovery; risk characteristics